2013
DOI: 10.1037/lhb0000010
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicated witnesses and suspects: An archival analysis of their involvement in criminal case processing.

Abstract: Research about intoxicated witnesses and criminal suspects is surprisingly limited, considering the police believe that they are quite ubiquitous. In the present study, we assessed the involvement of intoxicated witnesses and suspects in the investigation of rape, robbery and assault crimes by analyzing cases that were referred by the police to a prosecutor's office. Results indicated that intoxicated witnesses and suspects played an appreciable role in criminal investigations: Intoxicated witnesses were just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 28 publications
4
56
1
1
Order By: Relevance
“…Police surveys and archival research indicate that intoxicated witnesses and victims often provide police statements and take identification tests in criminal investigations (Evans, Schreiber Compo, & Russano, 2009; Palmer, Flowe, Takarangi, & Humphries, 2013). Yet, relatively few line‐up studies have examined the impact of alcohol on identification accuracy (Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm‐Gordh, 2013; Harvey, Kneller, & Campbell, 2013; Kneller & Harvey, 2016; Yuille & Tollestrup, 1990).…”
Section: Background: the Effects Of Alcohol On Identification Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Police surveys and archival research indicate that intoxicated witnesses and victims often provide police statements and take identification tests in criminal investigations (Evans, Schreiber Compo, & Russano, 2009; Palmer, Flowe, Takarangi, & Humphries, 2013). Yet, relatively few line‐up studies have examined the impact of alcohol on identification accuracy (Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm‐Gordh, 2013; Harvey, Kneller, & Campbell, 2013; Kneller & Harvey, 2016; Yuille & Tollestrup, 1990).…”
Section: Background: the Effects Of Alcohol On Identification Accuracymentioning
confidence: 99%
“…We also tested whether alcohol consumption and/or alcohol expectancy (i) weakens the confidence–accuracy relationship, as per the optimality hypothesis, or (ii) strengthens the confidence–accuracy relationship as per Palmer, Brewer et al's (2013) theory‐based information model of the confidence–accuracy relationship.…”
Section: Alcohol and Metamemory Judgments Of Line‐up Identification Amentioning
confidence: 99%
“…It is unclear if this is being conducted today, but 71% of US law enforcement officers reported several years ago that they do not measure the witnesses' intoxication level in an objective manner [5]. Similar, as noted by Palmer et al [6], police officers in the US usually determined that a witness had consumed alcohol or another drug because the witness reported this (in 88% of the cases). Few officers took a breathalyzer test (9%), or observed the witness engaging in alcohol or other drug intake (3%).…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 93%
“…A law-enforcement survey and an archival study found that alcohol-intoxicated witnesses to crimes are highly prevalent [5,6]. The survey of US police officers showed that intoxicated eyewitnesses were most commonly encountered in violent crimes, such as fights, domestic disputes, assaults, thefts and disorderly conduct.…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 99%
See 1 more Smart Citation